Control constitucional de los tributos con fines extrafiscales en el perú - Landa Arroyo, César (Pontificia Universidad Católica del Perú, 2013)
Traditionally, it has been understood that taxes have only a collection purpose. Nevertheless, our constitutional tax legal system has allowed the existence of extra tribute taxes, that is, those who pursue “something else” Are they constitutionally legitimate? In this article, and on the basis of thejurisprudence of the Constitutional Court of Peru, the author explains its content and their sustenance, as well as its limits: the principles of Constitutional Tax Law.

Tradicionalmente se ha entendido que los tributos sólo cuentan con un propósito recaudatorio. Sin embargo, nuestro sistema constitucional tributario ha permitido la existencia de los tributos extrafiscales; aquellos que persiguen “algo más” ¿Son acaso constitucionalmente legítimos? En este artículo, y sobre la base de la jurisprudencia del Tribunal Constitucional del Perú, el autor explica su contendido y su sustento, así como sus límites: Los principios del Derecho Constitucional Tributario.
Keywords: Law; Constitutional Law; Extra Tribute Taxes; Contributory Capacity; Tax Collection; Non-Confiscation; Equality; Derecho constitucional; Tributos extrafiscales; Capacidad contributiva; Recaudación tributaria; No confiscatoriedad; Igualdad; https://purl.org/pe-repo/ocde/ford#5.05.01